1988
DOI: 10.1007/bf01537966
|View full text |Cite
|
Sign up to set email alerts
|

Identity formation and social relations during late adolescence

Abstract: Theoretical assumptions outlined by Erik Erikson on psychosocial crisis resolution hypothesizes that the positive resolution of the identity crisis is predictive of more mature intimacy formation. To test this hypothesis, college-aged late adolescents (48 subjects) completed interviews and selfreport instruments measuring identity formation and degree of intimacy along with daily records of social interactions for one week. Analyses indicated a complex association between identity and intimacy formation. Compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
4

Year Published

1996
1996
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 21 publications
1
27
0
4
Order By: Relevance
“…Identity and relationship intimacy development may be a merged process for women whereas identity development may precede the emergence of relationship intimacy for men (Dyk & Adams, 1987). This interpersonal identity focus is associated with higher intimacy for women than men in opposite-sex relationships (Craig-Bray et al, 1988). As a result, our findings suggest women in less developed identity statuses may view their romantic relationships as being more intimate than men in similar identity statuses (i.e., identity diffuse, foreclosed, and moratorium).…”
Section: Identity Status Differences In Romantic Relationship Intimacymentioning
confidence: 75%
See 1 more Smart Citation
“…Identity and relationship intimacy development may be a merged process for women whereas identity development may precede the emergence of relationship intimacy for men (Dyk & Adams, 1987). This interpersonal identity focus is associated with higher intimacy for women than men in opposite-sex relationships (Craig-Bray et al, 1988). As a result, our findings suggest women in less developed identity statuses may view their romantic relationships as being more intimate than men in similar identity statuses (i.e., identity diffuse, foreclosed, and moratorium).…”
Section: Identity Status Differences In Romantic Relationship Intimacymentioning
confidence: 75%
“…However, individuals vary in their capacity for developing and maintaining these relationships, and one factor associated with the capacity for developing intimate romantic relationships is each member's identity commitment. Research has suggested that identity and intimacy progress concurrently during adolescence and emerging adulthood (Craig-Bray, Adams, & Dobson, 1988;Dyk & Adams, 1987;Loff et al, 2005;Paul & White, 1990), and individuals characterized as having made identity commitments may have more intimate romantic relationships than individuals characterized as not having made identity commitments. The relation between identity and intimacy has been theorized to differ for men and women (see Dyk & Adams, 1990;Josselson, 1987;Markstrom IDENTITY AND INTIMACY ASSOCIATIONS WITH WELL-BEING & Kalmanir, 2001).…”
Section: Identity Status As a Predictor Of Romantic Relationship Intimentioning
confidence: 96%
“…Due to the exploration associated with this transitory stage, emerging adults are in the process of examining their religious identity and beliefs (Erikson 1968;Marcia 1966). The ability to establish an identity has been shown to relate to the expression of self-esteem (Akhtar 1984;Craig-Bray et al 1988;Rothman 1984). Hence, a detailed examination of the relationship between religiosity and adjustment would further our understanding of the development of religious identity in emerging adulthood and the significant role it plays in other areas of a young adults' life.…”
Section: Introductionmentioning
confidence: 98%
“…Research suggests that in comparison to people who did not engage in exploration, identity achievers (individuals with exploration-based commitment) manifest higher epistemic thinking (Boyes & Chandler, 1992), deeper interpersonal relations (Craig-Bray, Adams, & Dobson, 1988), and better well-being (Meeus, Iedema, Helsen, & Vollebergh, 1999). Such individuals have been found to rely less on other's opinions during decision making (Kroger, 1996), to be more creative (Waterman & Archer, 1990), and to use rational and systematic decision-making strategies (Blustein & Phillips, 1990).…”
mentioning
confidence: 94%